CONTENT ANALYSIS IN EDUCATIONAL RESEARCH IN PHYSICAL EDUCATION: A STUDY ON CURRICULAR INTERNSHIP - Benites, Larissa Cerignoni [UNESP]; Nascimento, Juarez Vieira do; Milistetd, Michel; Farias, Gelcemar Oliveira (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2016)
This article is a step-by-step description of a study on teacher training in the context of curricular supervised internship in Physical Education. Using Bardin's (1979) content analysis procedures - pre-analysis, exploration of material, result processing, inference, and interpretation - it describes in detail the pathway adopted by researchers in the process of understanding the dialogue between school, assistant teacher, and student.
Keywords: Internship; Qualitative research; Teaching; Teachers